Effect of weight-bearing Liuzijue Qigong on cardiopulmonary function. Issue 8 (22nd February 2023) - Li, Desheng; Shen, Mei; Yang, Xiaoyan; Chen, Desheng; Zhou, Chunxiu; Qian, Qiuyang
Abstract : Background: Since the outbreak of coronavirus disease 2019, many people have had to reduce their outdoor activities. Therefore, a convenient, simple, at-home training method to improve or maintain cardiopulmonary function is required. This study aimed to explore the therapeutic effect of weight-bearing Liuzijue Qigong on cardiopulmonary function in healthy volunteers. Methods: This study was a longitudinal trial. The health participants completed a 4-week Liuzijue Qigong exercise with 0.25 kg sandbag wore on each wrist. Each training session took 30 minutes to complete 2 consecutive cycles, and 5 times a week. The cardiopulmonary function of participants was evaluated at baseline (T0) and the end of the intervention (T4). Outcomes measures were pulmonary function, diaphragm movement, and cardiac hemodynamic parameters. Paired t test was used to analyze differences within the group. Results: After 4 weeks of weight-bearing Liuzijue Qigong exercise intervention, the differences in the forced expiratory volume in the 1st second ( P = .006), forced vital capacity rate of 1 second ( P = .003), maximal mid-expiratory flow curve ( P = .002), forced expiratory flow at 50% of forced vital capacity ( P = .003), and maximum ventilatory volume ( P < .001) of the participants were statistically significant. The diaphragmatic excursion ( P = .009) under the calm breathing mode and the diaphragmatic contraction speed ( P = .003) under the deep breathing mode improved significantly. The cardiac output ( P = .04), cardiac index ( P = .035), contractility index ( P = .018), early diastolic filling ratio ( P = .042), systemic vascular resistance index ( P = .019), systemic vascular resistance ( P = .017), and estimated ejection fraction ( P = .016) of participants improved significantly in the resting stage. At the end stage of fast walking, that is, the sixth minute of six-minute walk test, the stroke volume index ( P = .048), heart rate ( P = .019), cardiac output ( P = .008), cardiac index ( P = .003), and left cardiac work index ( P = .028) of participants were significantly increased compared with those before training, and the systemic vascular resistance index ( P = .003) and systemic vascular resistance ( P = .005) were decreased. Conclusion: Weight-bearing Liuzijue Qigong training significantly improved cardiopulmonary function in healthy volunteers, thus representing home-based cardiopulmonary rehabilitation training.